Evaluation of psoralen ethosomes for topical delivery in rats by using in vivo microdialysis - Zhang YT (Dove Medical Press, 2014)
Yong-Tai Zhang, Li-Na Shen, Ji-Hui Zhao, Nian-Ping FengDepartment of Pharmaceutical Sciences, Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of ChinaAbstract: This study aimed to improve skin permeation and deposition of psoralen by using ethosomes and to investigate real-time drug release in the deep skin in rats. We used a uniform design method to evaluate the effects of different ethosome formulations on entrapment efficiency and drug skin deposition. Using in vitro and in vivo methods, we investigated skin penetration and release from psoralen-loaded ethosomes in comparison with an ethanol tincture. In in vitro studies, the use of ethosomes was associated with a 6.56-fold greater skin deposition of psoralen than that achieved with the use of the tincture. In vivo skin microdialysis showed that the peak concentration and area under the curve of psoralen from ethosomes were approximately 3.37 and 2.34 times higher, respectively, than those of psoralen from the tincture. Moreover, it revealed that the percutaneous permeability of ethosomes was greater when applied to the abdomen than when applied to the chest or scapulas. Enhanced permeation and skin deposition of psoralen delivered by ethosomes may help reduce toxicity and improve the efficacy of long-term psoralen treatment.Keywords: absorption enhancer, formulation vehicle, nanocarriers, nanoparticles, transdermal